WADI’AH SYIRKAH DAN MUDARABAH DALAM PERSPEKSTIF ISLAM - Armin, Muh (Dahzain Nur, 2022)
Journal entitled wadi’ah Syirkah and Mudharabah in an Islamic perspective. The Purpose it to find out what is meant by Syirkah and Mudharabah, The legal basis of syirkah and Mudharabah, the types of syirkah and Mudharabah. The results of the study show that Syirkah is a cooperation between two or more people in a business and the consequences of profits in Islam. Because its existence is strengthened by the Qur’an, hadith, ijma ulama. Mudharabah or Qiradl is giving capital from one person to another for business capital,while the profit for both is according to the peace (agreement) between the two during the contract, divided by two or divided by three, for example. Mudharabah has a basis from the Qur’an al-Sunnah, Ijma’ and qiyas. Broadly speaking, mudharabah is divided into two, namely mudharabah mutlaqah and mudharabah muqayyadah. A valid mudharabah contract must meet its pillars and conditions. There are five pillars of mudharabah, namely capital owners (sahibul maal), business actors or capital managers (mudarib), capital (ra’sul mal), capital management jobs, (al-‘amal) and profits (al-ribh). A valid mudharabah must meet the requirements. Conditions attached to the pillars. These conditions are as follows: first, the terms related to the parties to the contract, Second, the terms related to capital, and the third terms related to profits or profits. The implementation of mudharabah in Islamic financial institutions includes understanding (in the context of financing), application (in the context of financing), the practice of mudharabah financing